Vegetative Propagation of Kusum [Schleichera oleosa (Lour.) Oken] through Air Layering for the Mass Multiplication of Quality Planting Stock - Sheeraz Saleem Bhat; VD Lohot; S Ghosal; V Singhal; J Ghosh; N K Sinha; S Ahmad; NH Mir; A Regu (Archives of Current Research International, 2025)
Schleichera oleosa (Lour.) Oken, locally known as kusum (family Sapindaceae), is an important lac host tree, on which the lac insect (Kerria lacca), produces better quality lac, the kusmi lac Study on vegetative propagation of kusumwas undertaken during 2014-17 to generate quality planting stock through air layering in the Research Farm of the ICAR-Indian Institute of Natural Resins and Gums, Ranchi, Jharkhand. Sixteen phytohormone-medium combinations were taken for air layering, plus one already standardized for litchi as control, on kusum with 20 air layerings under each combination; 10 each with black polythene and 10 with transparent each year. The overall results revealed better rooting percentage during the pre-monsoon season (66 %) as compared to just 38 per cent during the monsoons, with black polythene in both seasons. During the pre-monsoon season, treatment combination with phyto-hormones in higher concentrations (IBA: NAA: Kinetin as 3000:1500:150) with media (sand: silt: clay: vermi compost: Sphagnum moss = 2:1:1:1:1) resulted in 100 per cent rooting. This was followed by combination with IBA: NAA: Kinetin as 2000:1000:100 and Sphagnum moss (90 %), which also resulted in highest rooting percentage (90 %) during the monsoon season. The detached air layering were hardened in the tree shade. Overall survival percentage of air layerings was 32.76 per cent. The technique can be helpful in mass propagation of true to type planting stock from plus trees or elite trees identified for lac production thereby increasing its productivity, germplasm conservation and management. The survival rate can be enhanced by providing better microclimate under hi-tech Poly houses at the early stages.